An investigation into the awareness, occurrence and preparedness for disaster management in selected academic libraries in Tanzania, East Africa (2013)
This study investigated the awareness, occurrence and preparedness to manage disaster in selected academic libraries in Tanzania. The study was conducted with a view to addressing the inefficiency in library disaster management and offers some suggestions on how to prepare before, during and after a disaster strikes in the library. Survey research technique was used to obtain data for the study. The population of the study consisted of all the 83 workers in the two libraries used for the study, because the responsibility for effective disaster management is collective. All the workers in the libraries were sampled because the population size is small. Five research questions guided the study and a questionnaire titled "Disaster Preparedness and Management Questionnaire" (DPMQ) containing 52 items was designed and administered to all the 84 members of staff used for this study. Fifty-one (51) copies out of 83 copies administered were returned, thus giving a respondent return rate of 61.4 per cent. The data collected were analyzed using percentages. The findings revealed that members of staff are aware of disaster in the library. However; there was no adequate preparation for its prevention and management. The study recommends that adequate funds should be provided to train staff, buy disaster kits, cultivate maintenance culture of the resources in the library, and create awareness, among others.